2009
DOI: 10.1002/app.30225
|View full text |Cite
|
Sign up to set email alerts
|

Polymer dynamics in rubbery epoxy networks/polyhedral oligomeric silsesquioxanes nanocomposites

Abstract: Dielectric techniques, including thermally stimulated depolarization currents (TSDC, À150 to 30 C) and, mainly, broadband dielectric relaxation spectroscopy (DRS, 10 À2 -10 6 Hz, À150 to 150 C) were employed, next to differential scanning calorimetry (DSC), to investigate molecular dynamics in rubbery epoxy networks prepared from diglycidyl ether of Bisphenol A (DGEBA) and poly (oxypropylene)diamine (Jeffamine D2000, molecular mass 2000) and modified with polyhedral oligomeric silsesquioxanes (POSS) units cova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 57 publications
(193 reference statements)
3
31
0
1
Order By: Relevance
“…Therefore, it is reasonable to assume that the same group is involved in these relaxations, i.e., epoxy group. [20][21][22] A similar behavior is observed for the c relaxation of both Jeff and JMF (where the relaxation times and activation energies also coincide). In addition, FTIR spectroscopy was employed to help in the identification of these dielectric signals through the analysis of the chemical species within the material.…”
Section: Reactants Characterizationsupporting
confidence: 76%
“…Therefore, it is reasonable to assume that the same group is involved in these relaxations, i.e., epoxy group. [20][21][22] A similar behavior is observed for the c relaxation of both Jeff and JMF (where the relaxation times and activation energies also coincide). In addition, FTIR spectroscopy was employed to help in the identification of these dielectric signals through the analysis of the chemical species within the material.…”
Section: Reactants Characterizationsupporting
confidence: 76%
“…A later study with thermal and dielectric methods confirmed slight plasticization on addition of the DGEBA-P monomers [170]. The results are discussed in terms of two contradictory effects, namely the loosened packing of chains and constraints to their mobility due to tethering on the rigid cages.…”
Section: Tethered Systemsmentioning
confidence: 72%
“…All techniques suggest a broadening of the distribution of relaxation times related to increased inhomogeneity. The dielectric study [170] revealed that α-relaxation is followed by the slower normal mode (NM) relaxation that reflects the orientation of the end-to-end vector of the macromolecular contour of POPD. This relaxation follows here the trends of α with respect to timescale.…”
Section: Tethered Systemsmentioning
confidence: 99%
“…At the same time, Table 1 clearly shows that the clay also decreases the T g of neat epoxy. Generally, nanofillers influence the T g of polymer matrices by two contradictory effects [38,39]: reduction of the chain mobility by interaction with the rigid nanofiller and (b) increase of the free volume because of the presence of the nanofiller and the loosened molecular packing of the chains. In the case of the rigid DGEBA-DDS network, the effect of the increased free volume dominates, leading to a decrease in the T g .…”
Section: Effect Of Clay On T Gmentioning
confidence: 99%